Population and overcrowding - Obadina, Tunde (Philadelphia, PA : Mason Crest, 2007)
Examines extreme overpopulation and poverty in various parts of Africa, increased mortality rates as a result of the AIDS epidemic, and high birth rates.
Includes bibliographical references (p. 100) and index.
8.9
5-8
Keywords: Overpopulation; Internal migration; Cities and towns -- Growth; Africa -- Population; Africa -- Social conditions; Africa -- Economic conditions